Decoding the mechanisms behind second primary cancers - Meiyuan Zeng; Anqi Lin; Aimin Jiang; Zhengang Qiu; Hongman Zhang; Shifu Chen; Mingyan Xu; Zaoqu Liu; Quan Cheng; Jian Zhang; Peng Luo (Journal of Translational Medicine)
Abstract Second Primary Cancers (SPCs) are defined as cancers that develop either simultaneously or metachronously in the same individual who has been diagnosed with and survived one primary cancer. SPCs exhibit a high incidence rate and represent the primary cause of mortality among survivors of first primary cancers. There is growing concern about the dangers of SPCs. This review summarizes recent studies on the mechanisms of SPCs, including the roles of genomic changes after first primary cancer (FPC) treatments, stromal cell phenotypic and metabolic changes, hormone levels and receptor expression, immunosuppression, aberrant gene methylation, EGFR signaling, and cell-free DNA in SPC development. This comprehensive analysis contributes to elucidating current research trends in SPC mechanisms and enhances our understanding of the underlying pathophysiology. Furthermore, potential applications of intratumoral microbes, single-cell multi-omics, and metabolomics in investigating SPC mechanisms are also discussed, providing new ideas for follow-up studies.